ANALISIS METODE BLENDED LEARNING TERHADAP INTERAKSI SISWA DALAM PROSES PEMBELAJARAN - Wijaya, Syahrul Andi; Bakhtiar, Afakhrul Masub (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2024)
The world of education continues to develop rapidly after the pandemic and presents various solutions. With the increasing number of learning methods available, and with increasingly varied learning. This article aims to provide an overview for teachers so they can use the Blended Learning learning method well and effectively. It is hoped that Blended Learning can be a solution for more interactive learning in learning. Both interactive between students and between teachers and students. The research method used in this article is literature study from various sources, both journals or results of previous researchers, as well as supporting books. The results of previous research are used in building conclusions.